Family, children and teachers' expectations about the first year of the nine-year Elementary School - Valéria Silva Ferreira (Universidade Federal de Santa Maria, 2013)
The Pedagogical Master Plan, for the nine-year Elementary School, should consider the socio-cultural and educational conditions of the children in the community as a guide to improve the quality of education. According to MEC guidelines (BRAZIL, 2004), one should not restrict the development of the six year old children exclusively to learning how to read. We know that family involvement with the school life of their children, maintaining constant contact with teachers and satisfied with the educational work, brings significant effects on student's learning (SCHEERENS; BOSKER, 1977; SCHEERENS , 2000). The current policy of MEC shows interest in mobilizing the involvement of the family and the school as a strategy for building an education of quality. This article discusses the results of a research that investigated the expectations of the involved actors (parents or guardians, children and teachers) regarding the anticipation of the enrollment age into Elementary School and the differences and similarities of these actors expectations. Parents and children were interviewed in their homes, in order to observe the literacy environment, and the first year teachers. What we observed in most homes is that the literate environment does not go beyond those that are part of everyday life of all households. The families hope that the school promotes a better and decent future for their children, countering the "myth of parental omission" (LAIHRE, 2004, p. 334). They try to assist their children with their homework and they demonstrate difficulties with their academic tasks, including two mothers who said they were illiterate.